Agricultural-induced environmental Kuznets curve for South Africa - Phiri, Andrew (Managing global transitions, 2025)
The purpose of the paper is to examine the impact of the agricultural sector on agricultural emissions in South Africa. To this end, we estimate an agricultural-induced environmental Kuznets curve (EKC) for South Africa between 1990 and 2022 using conventional and threshold regression frameworks. Our regression estimates reveal a ‘humped-shaped’ relationship between agricultural production and agricultural emissions, whereby agricultural production produces lower agricultural emissions above threshold estimates of 4,876 and 6,100 metric tons of CO2 emissions. Further investigations show that the South African economy has consistently remained above these thresholds since 2010. Moreover, a forecast analysis of the time series using ARIMA models shows that agricultural productionis (emissions are) on an upward (a downward) trajectory. However, the forecasting analysis also shows that the South African agricultural sector is not scheduled to reach the net-zero emissions target by 2050. Altogether, these findings imply that whilst South Africa had followed a trajectory of sustainable development prior to the COVID-19 pandemic, the current trajectory may not be sufficient to attain the 2050 Sustainable Development Goals.
Keywords: agricultural emissions; agricultural sector; ARIMA forecasting; environmental Kuznets curve (EKC); Južna Afrika; kmetijske emisije; kmetijski sektor; napovedovanje z ARIMA; okoljska Kuznetsova krivulja; pragovni regresijski model; South Africa; threshold regression model